Challenges of school-family-community partnerships in rural areas: a case study - Ribane, Motshekga Samuel (My University, 2022)
The study reports on an exploration of the challenges affecting School-Family Community partnerships in two secondary schools located in the remote rural areas of Mogodumo Circuit, in Lebowakgomo District in Limpopo Province, South Africa. The main research question answered was. What are the challenges of School-Family-Community partnerships in rural areas at Mogodumo Circuit in Limpopo Province? This study is qualitative in design and is embedded within the interpretive epistemology. The two secondary schools were conveniently sampled due to their accessibility whereas participants were also purposefully sampled. The number of participants sampled was n=32. Data was collected through documents analysis, semi-structured questionnaires involving sampled participants, and observation by the researcher as a silent and non-participant observer. Inductive analysis was applied to arrange and organise data in thematic categories. From the themes discovered, intervention strategies were developed in order to address the challenges affecting the School-Family-Community partnerships at the two rural secondary schools. The study revealed that there is little or no involvement of stakeholders such as parents, community leaders (including priests, pastors, headmen, and the chief), and community based businesspeople, and non-governmental organisations in school events, activities and functions. The study recommends that developmental programmes such as parenting, literacy and numeracy, and parent involvement in the education of their children be organised for parents and community members. These challenges affecting School-Family-Community partnerships need to be dealt with accordingly by the active involvement and engagement of various stakeholders including, more especially, the DBE, SMTs, NGOs, educators, learners, parents, various community members, and private sectors.
Thesis (M.Ed. (Community and Continuing Education)) -- University of Limpopo, 2022
Keywords: School-Family-Community Partnerships; Learner; Educator; Parent; Family; School; Community; Partnership; Parental involvement and Rural; Community and school -- South Africa -- Limpopo; Educators -- South Africa -- Limpopo; School management and organization -- Parent participation; High school students -- South Africa -- Limpopo; Education, Secondary Parent participation [150]